Self-esteem, perception of relationships, and emotional distress: A cross-cultural study - Abe, Jo Ann A (Personal Relationships, 2004)
This study examined the relative importance of self-esteem, family cohesion, and support from friends in predicting depressed mood and anxiety in Japanese and American college students. Contrary to expectations, self-esteem was the strongest predictor of emotional distress in both groups of students. Nevertheless, consistent with predictions derived from Markus and Kitayama's theory of self-construals, family cohesion accounted for a significantly larger percentage of the variance in predicting emotional distress in Japan than in the United States. In both countries, the relations between support from friends and the measures of emotional distress were entirely mediated by self-esteem. However, among Japanese students, family cohesion accounted for additional significant variance in predicting the measures of emotional distress, even after controlling for self-esteem.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-511-906-572-838 tex.type: [object Object]
Keywords: dept.psy